Efeito probiótico do Bacillus amyloliquefaciens no desempenho produtivo e nos parâmetros hematológicos, morfométricos e ultraestruturais do intestino de tilápias-do-Nilo cultivadas em tanque-rede - Silva, Thiago Fernandes Alves [UNESP] (2014)
The aim of this study was to evaluate the probiotic effect of Bacillus amyloliquefaciens on productive performance, hematological profile, morphology and ultrastructure of the intestine in the Nile tilapia (Oreochromis niloticus) reared in cages. A total of 936 Nile tilapias were distributed in 12 cages in a completely randomized design consisting of four treatments and three replications. The animals were fed for 90 days (3% biomass / day) with concentrations of probiotic included in commercial diets: 0 (control); 1 × 106 CFU·g -1 (T1); 5 × 106 CFU·g-1 (T2); and 1 × 107 CFU·g-1 (T3). The results were subjected to analysis of variance (ANOVA) and when significant by Tukey's test (P <0.05). There was no difference in growth performance and proximate composition. The glucose level and hemoglobin were lower in the group receiving the highest concentration of probiotic compared to the control group indicating that it may have an effect in increasing the homeostatic level. Others haematological indices presented no differences. There was growth of the villi and the number of goblet cells of the intestine in treated groups, which results in improved digestion and absorption of nutrients by the fish. The scanning photomicrographs of the gastrointestinal tract showed no presence of B. amyloliquefaciens. This may be especially the amount of bacteria supplied with the environmental conditions of cultivation. These results allow us to conclude that under the conditions tested, B. amyloliquefaciens showed no sufficient effect on growth performance. However, increased intestinal villi, goblet cell number and increased homeostasis level observed in this study could mean a higher state of health in the animal